Transcriptional and posttranscriptional regulation of Shigella shuT in response to host‐associated iron availability and temperature. Issue 3 (26th January 2017) - Wei, Yahan; Kouse, Andrew B.; Murphy, Erin R.
Abstract: Like most bacteria, Shigella must maintain a precise balance between the necessity and toxicity of iron; a balance that is achieved, at least in part, by regulating the production of bacterial iron acquisition systems in response to specific environmental signals. Using the Shigella heme utilization (Shu) system, S. dysenteriae is able to acquire iron from heme, a potentially rich source of nutritional iron within the otherwise iron‐limited environment of the human host. Investigations presented within reveal two distinct molecular mechanisms underlying previously uncharacterized transcriptional and translational regulation of shuT, a gene encoding the periplasmic‐binding component of the Shu system. While shuT transcription is regulated in response to iron availability via a process dependent upon the global regulator Fur and a Fur‐binding site located immediately downstream of the promoter, shuT translation is regulated in response to environmental temperature via the activity of an RNA thermometer located within the 5′ untranslated region of the gene. Such complex regulation likely increases the fitness of S. dysenteriae by ensuring maximal ShuT production when the pathogen is within the iron‐limited and relatively warm environment of the infected host, the only environment in which heme will be encountered as a potential source of essential iron. Abstract : This study focuses on characterizing the effect of host‐specific environmental signals on the production of Shigella dysenteriae ShuT, a component of the S. dysenteriae heme‐uptake systems. Specifically the work demonstrates that shuT transcription is regulated in response to iron availability by the global regulator Fur and that translation is regulated in response to environmental temperature via the activity of a cis‐acting RNA thermometer. This multilevel regulation ensures maximal production of ShuT when the bacterium is growing in a warm, iron‐poor environment, like that encountered in the human host; the only environment in which S. dysenteriae will encounter heme as a potential source of essential iron.